DAYA TARIK BUNGA SAKURA BAGI MASYARAKAT JEPANG - Nur Hastuti (IZUMI, 2015)
Sakura is the pride flower of Japanese from the past.  Many person can enjoy the beauty of Sakura. Sakura usually blossoms in the spring season, begins from south Japan region in the middle of March and continue to the norh Japan ( in the middle of April up to end of April). During spring season, mass media reports about Zensen Sakura, that is prediction the growth of Sakura in many places in Japan, along with climate prediction. By that information, Japanese people are ready to welcome warmer air in the spring ( after winter) and holding Hanami feast. Based on that situation, writer interest to write this research by the title “ The Attraction of Sakura Flower for Japanese people”. The problem that will be analized is how is the attraction and the effect of Sakura flower for Japanese people. In this research, writer uses literary review from internet, article, and many other sources. The attraction of Sakura flower is Japanese people can enjoy Hanami with family, friends, and close person in the office and organization.  The effect of Sakura in Japanese life is very important, like to raise the affection in the family, make closer the friendship,and make better communication with partner or relation.